HOW DO E-WORKSHEET USING WIZER.ME BASED GOOGLE SITE IMPROVE HIGHER ORDER THINKING SKILLS AND COMMUNICATION SKILLS? (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2023)
Higher Order Thinking Skills (HOTS) and Communication Skills (CS) must be taught to pre-service physics teacher in the twenty-first century if they are to become future professional physics teacher. Based on the results of the preliminary study it is known that the HOTS and CV categories of physics education students are still lacking with an average score of 25 and 3. In addition, learning time in class is limited to solving problems so lecturers want to take advantage of technology in making teaching materials that facilitate independent practice outside the classroom, easily accessible to pre-service physics teacher (paperless), easy to provide feedback and correction results from worksheets so that learning evaluation is more effective and efficient. One treatment that can be applied to train HOTS and CS is to use teaching materials in the form of electronic-worksheets (e-worksheets) using Wizer.me based Google Site. E-worksheets will be more optimal if applied in learning, namely the Contextual Teaching and Learning (CTL) model and the Blended Problem-Based Learning (B-PBL) model. The purpose of this study was to determine the effectiveness of e-worksheets in CTL and B-PBL using Wizer.me based Google Site, changes to HOTS and CS and to determine student perceptions of using e-worksheets. The research method is quasi-experimental with a two-treatment counterbalanced design. The population of this study was all statistical physics classes for the 2022/2023 academic year, consisting of 2 classes with a total of 66 students. The sampling technique was purposive sampling, with 33 students in each class. Data collection techniques used the HOTS test, communication skills observation sheets and perception questionnaires about the use of CTL and B-PBL-based e-worksheets. The HOTS test is in the form of a description with a total of 3 questions including analyzing (C4), evaluating (C5) and creating (C4). Communication skills observation sheets include systematics/format, use of language, completeness and sequence of contents. The perception questionnaire consists of 9 questions using the Guttman scale. Based on the results of data analysis, it is known that CTL and B-PBL-based e-worksheets are effective in training HOTS and CS with large categories, namely 0.88 and 0.91. The increase in HOTS and CS was in the high category in both classes but the increase in the BPBL-CTL class was better with N-Gain, namely 0.87 and 0.92. The results of the questionnaire analysis stated that physics education students gave a good response with almost all students stating that the use of e-worksheets using Wizer.me based Google Site could increase HOTS and CS and physics education students were more independent in finding solutions to problems. Based on the results of data analysis, it can be concluded that e-worksheets in CTL and B-PBL using Wizer.me based Google Site can increase HOTS and CS.
Keywords: e-worksheet; CTL; B-PBL; HOTS; communication skills